Portret van een man met een ring van Jan van Eyck - van Asperen de Boer, J. R. J.; Ridderbos, B.; Zeldenrust, M. (The Rijksmuseum Bulletin, 1991)
This special issue of the Bulletin is devoted to the restoration and the art-historical and scientific examination of the four paintings from the Art Museum of the Republic of Romania in Bucharest, which were brought to this country at the beginning of 1990 in order to be restored and examined under the auspices of the Rijksmuseum in the context of the aid programme for this badly hit museum. It gives us great pleasure to be able to offer this bilingual publication, scheduled to accompany the presentation of the paintings, which will remain on exhibition for a month in one of the side rooms of the Gallery of Honour.THE EDITORS